Mapping climate adaptation finance in Kenya's devolved governance system: A case of Makueni County - Judith Mulwa; Marie Ladekjær Gravesen (Danish Institute for International Studies (DIIS), 2022)
This paper analyses the four main types of expenditures of both national and international sources of public funds by the Kenyan ministries based on both Kenyan national budget data and the most relevant disbursement for financing climate activities. Kenya is among the first countries to develop policies, strategies and institutional frameworks for climate action, creating a policy and legal environment to advance an effective climate change response, similarly, Makueni County (in Kenya) has also enacted county-level regulation on climate change as part of the implementation of the national agenda on climate change. The climate-related expenditures that were tracked represent 18% of total government development expenditures for the fiscal year 2017/18. The research team uses the case of Makueni County to understand levels of devolution by analysing the streams of income from the national budget to the county budget that are channelled towards climate-related activities at the county level. Preliminary analysis shows a strong correlation between climate-friendly policies and the flow of funds for climate change at the county level. Other factors include the establishment of a local climate change fund through the County Climate Change Fund mechanism (CCCF). These factors have enabled the counties to create, access and use climate finance to build communities' resilience and reduce vulnerabilities to climate change in a coordinated way. This analysis is an initial step of the four-year comparative research programme, GAP, looking at the governance of climate change adaptation finance in the Kenya compared to Tanzania. The working paper serves to lay a foundation for further in- depth research.
Keywords: 330; CCCF; Kenya; GAP; Governing Adaptation Finance for Transformation; climate change adaptation finance; climate change fund; climate change fund mechanism